Cultural Hurdles and Family Restrictions on Female Political Participation among Representatives to the Union Parishads of Bangladesh - Haque Talukdar, Imdadul; Österman, Karin; Björkqvist, Kaj (Technium Social Sciences Journal, 2021)
The aim of the study was to investigate cultural hurdles and family restrictions on female political participation among representatives to the Union Parishads of Bangladesh. A questionnaire was completed by 680 representatives from 128 Union Parishads, the rural local governance, of Bangladesh (347 females, 333 males). The mean age was 42.6 years (SD = 6.4) for females and 43.9 (SD = 6.2) for males. A questionnaire was constructed for measuring political participation, experiences of females and observations by males regarding cultural hurdles and family restrictions on female political participation. The amount of both cultural hurdles and family restrictions experienced by female representatives were significantly higher than the amounts their male colleagues had observed. Women with low levels of political participation had experienced high levels of cultural hurdles and low levels of family restrictions. Women with high levels of political participation experienced low levels of cultural hurdles and high levels of family restrictions. For females, age correlated negatively with cultural hurdles but not with family restrictions. Female political participation in the Union Parishads of Bangladesh is hampered by both cultural hurdles and family restrictions. Male colleagues did not observe the full amount of hurdles that females experienced.